GoBIS: An integrated framework to analyse the goal and business process perspectives in information systems. (October 2015) - Ruiz, Marcela; Costal, Dolors; España, Sergio; Franch, Xavier; Pastor, Óscar
Abstract: Context: Organisational reengineering, continuous process improvement, alignment among complementary analysis perspectives, and information traceability are some current motivations to promote investment and scientific effort for integrating goal and business process perspectives. Providing support to integrate information systems analysis becomes a challenge in this complex setting. Objective: The GoBIS framework integrates two goal and business process modelling approaches: i ⁎ (a goal-oriented modelling method) and Communication Analysis (a communication-oriented business process modelling method). Method: In this paper, we describe the methodological integration of both methods with the aim of fulfilling several criteria: i) to rely on appropriate theories; ii) to provide abstract and concrete syntaxes; iii) to provide scenarios of application; iv) to develop tool support; v) to provide demonstrable benefits to potential adopters. Results: We provide guidelines for using the two modelling methods in a top-down analysis scenario. The guidelines are validated by means of a comparative experiment and a focus-group session with students. Conclusions: From a practitioner viewpoint (modeller and/or analyst), the guidelines facilitate the traceability between goal and business process models, the experimental results highlight the benefits of GoBIS in performance and usability perceptions, and demonstrate an improvement on the completeness of the latter having an impact on efficiency. From a researcher perspective, the validation has produced useful feedback for future research.